2020
DOI: 10.1590/s1678-86212020000400482
|View full text |Cite
|
Sign up to set email alerts
|

Isolamento do ruído de impacto no sistema de piso com aplicação de revestimento sobre o piso original

Abstract: Resumo A classificação de desempenho acústico ao ruído de impacto em sistemas de piso prevista na NBR 15575-3 (ABNT, 2013) é exigência apenas às novas construções de edifícios multipavimentos. O presente artigo aborda tais problemas de ruídos que ocorrem nos edifícios concluídos antes de 2013. O estudo busca uma alternativa para a correção acústica, através da aplicação de novo revestimento sobre piso original. Para tal considerou-se os seguintes condicionantes: facilidade de execução e menor acréscimo na espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
(9 reference statements)
1
0
0
Order By: Relevance
“…The results in Figures 12 to 15 are consistent with the studies that highlighted the importance of using resilient materials in order to obtain greater insulation from impact noise in floor systems (HOPKINS, 2012;OLIVEIRA et al, 2021;PANOSSO;PAUL, 2020;XAVIER;FERREIRA, 2020). When analyzing the samples with floating floor (S13 to S39), it was observed that there was a decay of sound levels from the 160 Hz band in all samples.…”
Section: Resultssupporting
confidence: 83%
“…The results in Figures 12 to 15 are consistent with the studies that highlighted the importance of using resilient materials in order to obtain greater insulation from impact noise in floor systems (HOPKINS, 2012;OLIVEIRA et al, 2021;PANOSSO;PAUL, 2020;XAVIER;FERREIRA, 2020). When analyzing the samples with floating floor (S13 to S39), it was observed that there was a decay of sound levels from the 160 Hz band in all samples.…”
Section: Resultssupporting
confidence: 83%